Hambatan Implementasi Kebijakan Pengelolaan Sampah Rumah Tangga di Kota Binjai - Putranto Manalu; Fahmi Syahpreza Tarigan; Ermi Girsang; Chrismis Novalinda Ginting (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2022)
Latar belakang: Pengelolaan sampah merupakan permasalahan penting yang harus diprioritaskan oleh pemerintah mengingat pertumbuhan penduduk yang cukup masif yang berimplikasi pada meningkatnya volume sampah yang dihasilkan. Implementasi kebijakan pengelolaan sampah di Kota Binjai masih belum optimal yang diindikasikan peningkatan volume sampah tiap tahunnya. Studi ini bertujuan mengevaluasi implementasi kebijakan pengelolaan sampah rumah tangga dan sampah sejenis sampah rumah tangga di Kota Binjai.Metode: Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Penentuan subjek penelitian menggunakan teknik purposive sampling. Subjek penelitian terdiri dari kepala UPTD Pengolahan Sampah dan TPA Dinas Lingkungan Hidup Kota Binjai, kepala sub bagian umum dan kepegawaian Dinas Lingkungan Hidup Kota Binjai, dan 2 orang fasilitator lapangan UPTD Pengolahan Sampah dan TPA Dinas Lingkungan Hidup Kota Binjai sebagai informan triangulasi. Adapun variabel yang diteliti adalah komunikasi, sumberdaya, disposisi dan struktur birokrasi. Dalam menggumpulkan data, peneliti melakukan wawancara mendalam, pengamatan langsung dan studi dokumen. Data dianalisis dengan model interaktif berupa analisis kualitatif yang disajikan dalam bentuk deskriptitif dan narasi yang menyertainya.Hasil: Pada studi ini ditemukan hambatan implementasi kebijakan pengelolaan sampah rumah tangga di Kota Binjai antara lain tidak adanya peraturan daerah yang spesifik mengenai pengelolaan sampah rumah tangga dan berakibat pada ketersediaan anggaran. Dukungan pimpinan yang kurang untuk menjadikan program ini sebagai program prioritas menjadi kendala lainnya. Sumber daya manusia yang tersedia secara kuantitatif cukup namun secara kualitatif sangat kurang, serta masih banyak sumber daya yang kurang produktif dalam menjalankan tugasnya.Simpulan: Implementasi pengolahan sampah rumah tangga menghadapi hambatan dari sisi regulasi pendukung, anggaran dan SDM yang kurang memadai, dan minimnya dukungan pimpinan. Dengan berbagai hambatan tersebut, penting bagi stakeholder untuk memprioritaskan penyusunan peraturan daerah pendukung kebijakan strategi nasional pengolahan sampah rumah tangga (Jakstranas) agar pelaksanaan kegiatan memiliki payung hukum yang jelas. Selain itu, penempatan SDM yang kompeten dan sesuai keahliannya dapat membantu mengatasi hambatan teknis pelaksanan kegiatan di lapangan. ABSTRACT Title: Barriers to the Implementation of Household Waste Management Policies in Binjai CityBackground: Waste management is one of the paramount issue that must be prioritized by the government, given the relatively rapid population growth that impacts the increase of waste volume being generated. The waste management policy implementation at Binjai City is not yet optimal indicated by the increase of waste volume annually. This study serves to evaluate the household waste management policy implementation and household-like waste at Binjai City.Method: This research is qualitative research with case study approach. Subjects consisted of the head of Waste Treatment and Final Processing Site of the Regional Environmental Office of Binjai City, the head of the general and staffing sub-section of the Regional Environmental Office of Binjai City, and 2 field facilitators of the Waste Treatment and Final Processing Site of the Regional Environmental Office of Binjai City as triangulation informants. The variables studied were communication, resources, disposition, and bureaucratic structure. The determination of research subjects was conducted through the purposive sampling technique. For data collection the researchers conducted in-depth interview, direct observation and literature study. The data were analyzed using an interactive model in the form of the qualitative analysis presented in the descriptive form and accompanying narration.Result: For this research, several barriers were found for the household waste management policy implementation at Binjai City, such as the lack of specific regional regulations concerning household waste management and in which it was affected by the budget availability. The lack of leadership support to make this program as a priority program was also found to be another obstacle. The human resources available in a sufficient quantitative manner does not translate well in quality sense, and there were still many less productive human resources performing their duties.Conclusion: The implementation of household waste management faces barriers in terms of supporting regulations, inadequate budgets and human resources, and lack of leadership support. Through such barriers, it is crucial for the stakeholders to prioritize the preparation of supporting regional regulations for national strategy for managing household waste policy (Jakstranas) in order for such implementation to have clear legal basis. Additionally, the placement of competent human resource and in accordance with their expertise could facilitate to overcome the technical obstacles in implementing such activities on the field.